(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background:In Iraq, breast cancer is the commonest type of malignancy in females. The disease is a genetically and clinically heterogeneous. The cholesterol metabolite 27-Hydroxycholesterol (27HC), a primary metabolite of cholesterol and an estrogen receptor (ER) and Liver X receptor (LXR) ligand, increases ER-positive breast cancer. 27-hydroxycholesterol (27HC) is metabolized by oxysterol 7?-hydroxylase (CYP7B1), CYP7B1 expression has been decreased in ER-positive tumors compared with normal breast tissues. Objective: To study and investigate the possible association of clinic-pathological parameters 27HC and CYP7B1 level in sera of women with benign and malignant breast tumors and in control group by ELISA technique and Investigate the possible relationships of 27HC with CYP7B1. Methods: This case control study was conducted on sixty patients with breast diseases were divided into three group, group I contained twenty patients with benign breast diseases, group II consisted of twenty premenopausal patients with breast cancer. Group III comprised twenty postmenopausal patients with breast cancer with the mean age and standard deviation (25.25±7.87, 38.65±6.28, 58.5±7.02 years). 27HC and CYP7B1 were measured in tissues by instrument ELISA technique. Results: The tissue homogenates of women with premenopausal and postmenopausal breast cancer groups showed a significant elevation of 27HC in comparison with benign (p> 0.001), whereas there is no significant difference observed between both breast cancer groups (p= 0.542). The tissue homogenates of women with premenopausal and postmenopausal breast cancer groups showed a significant decrease of CYP7B1 concentration in comparison with benign (p= 0.003) and (p= 0.001), whereas there is no significant difference observed between both breast cancer groups (p= 0.868). Conclusion: A higher incidence of 27HC and a lower incidence CYP7B1 were obtained in malignant than benign breast tumor tissues with positive estrogen receptors. These indicate that the levels of 27HC and CYP7B1 in breast tumor tissues may be used as new biochemical markers for breast tumor prognosis. Keywords: 27-Hydoxycholesterol, CYP7B1, breast cancer, estrogen receptor Citation: Mohammed ZK, AL-Saeed HH, Nile AK. The level of 27-hydroxycholesterol and oxysterol 7?-hydroxylase (CYP7B1) in tissues of women with breast tumors. Iraqi JMS. 2018; 16(2): 201-206. doi: 10.22578/IJMS.16.2.12